Rations for performance testing bulls on a 140-day gain trial - McKee, M.; Evans, J.D.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
Twenty-six Angus, Hereford, and Shorthorn bull calves were started on feed November 16, 1970, to study differences in protein content of rations. The bulls were from 184 to 302 days old. They were randomly assigned within breeds to one of three grain rations (see table 45) and individually fed free choice. The prairie hay they would clean up in 30 minutes was fed twice a day. They went from their pens into a large lot to exercise together approximately four hours a day.
Keywords: Beef; Rations; Gain; Performance